σS-Mediated Stress Response Induced by Outer Membrane Perturbation Dampens Virulence in Salmonella enterica serovar Typhimurium - Kim, Seul I; Kim, Eunsuk; Yoon, Hyunjin (Frontiers in Microbiology, 2021)
Salmonella alters cellular processes as a strategy to improve its intracellular fitness during host infection. Alternative σ factors are known to rewire cellular transcriptional regulation in response to environmental stressors. σs factor encoded by the rpoS gene is a key regulator required for eliciting the general stress response in many proteobacteria. In this study, Salmonella Typhimurium deprived of an outer membrane protein YcfR was attenuated in intracellular survival and exhibited downregulation in Salmonella pathogenicity island-2 (SPI-2) genes. This decreased SPI-2 expression caused by the outer membrane perturbation was abolished in the absence of rpoS. Interestingly, regardless of the defects in the outer membrane integrity, RpoS overproduction decreased transcription from the common promoter of ssrA and ssrB, which encode a two-component regulatory system for SPI-2. RpoS was found to compete with RpoD for binding to the PssrA region, and its binding activity with RNA polymerase to form Eσs holoenzyme was stimulated by the small regulatory protein Crl. This study demonstrates that Salmonella undergoing RpoS-associated stress responses due to impaired envelope integrity may reciprocally downregulate the expression of SPI-2 genes to reduce its virulence.